Error Analysis in the Malay Language Essay Writing of Lower Secondary Students in Brunei Darussalam - Asnola, Wafiqah; Maswandi, Elmy; Zulkiflee, Zulfadzlee (Melayu: Jurnal Antarabangsa Dunia Melayu, 2022)
This study was conducted to identify errors in morphology, semantics and orthography in the written essays of lower secondary school students in Brunei Darussalam. The analytical approach used was Linguistic Category Taxonomy, which was introduced by Burt, Dulay and Krashen (1982). This study used both qualitative and quantitative methods to identify language errors and their percentages. Three samples of essays were randomly selected from lower secondary students’ assignments, which were collected from different schools in Brunei-Muara District, Brunei Darussalam. The research findings showed that there were a total of 104 language errors. Orthographic errors were the most frequent type of error (73%), followed by morphological errors (25%) and semantic errors (2%). Among the most common errors made were the incorrect use of uppercase and lowercase letters, the incorrect use of punctuation, the incorrect use of words influenced by the native and foreign languages and also the incorrect use of affixes. As a suggestion, intensive teaching and training should be applied to students. Besides that, teachers should also take various creative initiatives as effective teaching techniques.